Functional outcomes in total talus reconstruction with triangular double-barrel free fibula flap following oncological resection: A retrospective case series review. Issue 2 (February 2022) - Rosli, Mohamad Aizat; Sulaiman, Wan Azman Wan; Ismail, Wan Faisham Wan; Yahaya, Sahran; Saad, Arman Zaharil Mat; Wan, Zulmi; Halim, Ahmad Sukari
Summary: Background: With the advent of new techniques, foot salvage is feasible following talus oncological resection. As the reconstruction aims to achieve a pain-free, stable ankle for ambulation, biological limb reconstruction is the best option. This case series will evaluate the primary indications, complications, and functional outcomes of the reconstructed talus and highlighting the technical aspects of the surgery with a novel technique of triangular double-barrel free fibula flap. Methods: We performed a retrospective case note review of patients undergoing foot salvage surgeries and primary talus reconstruction with double-barrel free fibula flaps between 2009 and 2019. Patient demographics, aetiologies, operative details, complications, and outcomes were analysed. All patients underwent the same talar reconstruction technique whereby a wide-based triangular framework was created from two bony struts of the osteotomized fibula. The Musculoskeletal Tumour Society (MSTS) scoring system was used to analyse the short- to mid-term functional outcomes. Results: Four consecutive patients with aggressive benign and malignant tumours were identified. They consist of three males and one female, with a median age of 32 (range 27–39). Patients were followed up for a median duration of 60 months (range 24–132). Two flaps were complicated with venous thromboses; however, all were salvageable following re-explorations. All patients achieved solid bony fusion with good functional and aesthetic outcomes. The median MSTS score was 74.5% (range 66–76). No donor site morbidity and local recurrence were reported. Conclusion: The triangular double-barrel free fibular flap is a good option for limb salvage following total talus resection, with good short- to mid-term functional and aesthetic outcomes.